4
$\begingroup$

Suppose $x_1$ and $x_2$ are independent Poisson random variables with parameters equal to $\lambda_1$ and $\lambda_2$ respectively. Show the sum of $x_1$ and $x_2$ is also a Poisson random variable using the moment generating function.

I know the function for Poisson is $\frac{\lambda^x e^{-\lambda}}{x!}$ and moment for it is $M_x(t) = e^{\lambda(e^t - 1)}$.

So I have to show $M_{x_1 + x_2}(t)$ is of the form $e^{k(e^t - 1)}$. But I don't know where to plug in $\frac{\lambda^{x_1} e^{-\lambda}}{x_1!} + \frac{\lambda^{x_2} e^{-\lambda}}{x_2!}$ into the moment function.

$\endgroup$
4
$\begingroup$

By a basic "law of exponentiation" we have $$e^{\lambda_1(e^t-1)}e^{\lambda_2(e^t-1)}=e^{(\lambda_1+\lambda_2)(e^t-1)}.$$

$\endgroup$
  • $\begingroup$ I specifically used the mgf. $\endgroup$ – André Nicolas May 17 '14 at 1:16
4
$\begingroup$

You have to use the fact that if the random variables are independent, then the MGF of the sum is the product of the MGFS.

$$M_{X_1+X_2}(t) = M_{X_1}(t) M_{X_2}(t).$$

$\endgroup$
  • $\begingroup$ Do you know where I can find a proof for this? $\endgroup$ – mr eyeglasses May 17 '14 at 1:30
  • 2
    $\begingroup$ It follows from the definition. Since they're independent, $$E(e^{t(X+Y)}) = E(e^{tX})E(e^{tY})$$ $\endgroup$ – Fred May 17 '14 at 1:34

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.